SENTIDOS E IMPLICAÇÕES DA GESTÃO UNIVERSITÁRIA PARA OS GESTORES UNIVERSITÁRIOS - Osmailda da Fonseca Gomes (Universidade Federal de Santa Catarina, 2013)
This study aimed to understand the meanings and implications of university management for senior managers of Universidade Federal de Minas Gerais. Specific objectives verified the idea of management for the university manager and identified the implication of management in the personal and professional lives of universities’ manager. The method used for data collection was oral history and retrieval of words through interviews. For analysis was used analysis of content. The survey results indicate that the idea of university management is formed from the teaching until the manager's learning in administrative positions. About the implication in professional life were identified improvement in the acquisition of leadership, satisfaction for contributing to the academic community, improvement in managerial ability and decrease the contact with field of work. About implications for personal life were identified gain with the value of human and improvement management of conflict in personal life. However it was identified less time for family, leisure and vacation and less physical activities, it supporting a poor health and increased stress. We conclude that there is much to be improved in the management of university regarding your complexity about the accumulation of teacher and manager’s positions.